MRI-ultrasound fusion targeted transperineal prostate biopsy under local anaesthesia ‒ patient-reported and biopsy outcomes: a single centre cohort study - Mohd Ghani, Khairul Asri; Jaharudin, Mohd Azrul Eimirul; Khor Wei Shen, Vincent; Yusof, Mohd Razaleigh; Mohamad Sharin, Mohamad Fairuz; Jagwani, Arvind Vashdev; Lee, Fei Yee; Lee, Christopher Kheng Siang; Fahmy Ahmed, Omar Ahmed (Bionika Media, 2024)
Objective: To compare the tolerability and feasibility of transrectal(TR) versus transperineal (TP) routes for prostate biopsy under local anaesthesia(LA). To assess the functional outcome and the complication of both procedures. Methods. A prospective cohort observational study was performed on patients who underwent prostate biopsy under LA. Visual Analogue Scale (VAS) was used during the procedure. International Prostate Symptoms Score (IPSS) and International Index of Erectile dysfunction (IIEF) were assessed before the procedure and in 14 days after the procedure. Complication for each procedure was recorded. Result. A total of 128 patients with 64 patients for each group underwent prostate biopsy by TP and TR under LA. TP targeted biopsy group had comparable pain scores to those who underwent the procedure using the TR routes. The median pain score for the TP group was 2 and TR was 3, (IQR=2, range 0–10 for both groups)with no significant pain difference between both groups (P=0.48). Furthermore, there was no significant difference in urinary function(p=0.68) and sexual function (p=0.19) between the two groups post-procedure. Both groups have similar rates of complications, with no significant difference observed. Urinary tract infection incidents that did occur were rare and did not significantly differ between the groups (p=0.21). None of the patients experienced sepsis postoperatively. AUR was reported in both groups, slightly higher with 9.4%(N=6) in the TP group and 6.3%(N=4) in the TR group however no significant difference(p=0.112) was noted. Haematuria is common in both groups with TP (66%) and TR (59%) but self-limiting with Clavien-Dindo grade I without significant difference (p=0.589). Conclusion. Our results showed that both Transperineal and transrectal approaches have similar toler-ability with no significant difference in functional outcome or complications. Further studies are mandatory to verify our results.